Probative Value of KPPU Decisions in Bid Rigging Corruption under Law Number 20 of 2025 - Adhitya Miasa Sengaji; Rohaini Rohaini; Kasmawati Kasmawati; Sepriyadi Adhan S; Yennie Agustin (Corruptio, 2026)
Bid rigging reflects the intersection between competition law and corruption, particularly where collusive procurement practices result in state financial losses. This study examines the legal status and probative value of decisions issued by the Business Competition Supervisory Commission (KPPU) as documentary evidence in corruption investigations following the enactment of Law Number 20 of 2025 on the Criminal Procedure Code (KUHAP). The research employs a normative legal methodology using statutory and conceptual approaches. The findings show that final and binding (inkracht) KPPU decisions constitute admissible documentary evidence under the new KUHAP because they contain objective factual findings concerning the actus reus of bid-rigging. These findings also provide persuasive evidence from which investigators may infer mens rea, subject to corroboration with other admissible evidence. The recognition of KPPU decisions strengthens corruption investigations by enabling investigators from the Police, the Attorney General's Office, and the Corruption Eradication Commission (KPK) to build upon established findings of collusive conduct while coordinating with authorized audit institutions to establish state financial losses. The study recommends adopting cross-institutional technical regulations to facilitate digital evidence sharing and interoperability between the KPPU and criminal justice agencies, thereby improving investigative efficiency and supporting the principle of a speedy trial in procurement-related corruption cases..